PERCEPTION OF PHYSIOTHERAPY STUDENTS TOWARDS SPECIALIZATION IN GERIATRIC PHYSIOTHERAPY IN SOUTH-WEST NIGERIA (Journal of Biomedical Investigation, 2024)
Background: As the global geriatric population increases, so does the demand for specialized physiotherapy services to address the unique health challenges of older individuals. However, there is a growing shortage of geriatric physiotherapist specialists, which may adversely affect the care of elderly individuals at risk of chronic conditions, immobility, and falls.Aim of the Study: The study aimed to explore the perception of physiotherapy students towards specialization in Geriatric Physiotherapy, in South-West Nigeria.Materials and Methods: This is a cross-sectional survey involving 264 clinical physiotherapy undergraduates in South-West Nigeria. Participants were assessed using a questionnaire, adapted from a previous similar study. Data was analyzed using descriptive statistics and inferential statistics of Chi-square test, at
Keywords: Perception; Physiotherapy; Specialization; Geriatric Physiotherapy